Insights from Surveys on Business and Enterprises in South Sudan : Jobs, Recovery, and Peacebuilding in Urban South Sudan – Technical Report IV - Finn, Arden; von der Goltz, Jan (World Bank, Washington, DC, 2020)
This study assesses jobs in businesses and NGOs in the towns of South Sudan. It is based on a 2019 business survey that includes informal and micro enterprises, as well as a dedicated survey of foreign-owned businesses. The business community is typical of a low-income post-conflict country, but with a particularly weak productive sector and an outsize importance of NGOs and foreign-owned businesses. Two in five commercial businesses are foreign-owned; they employ far more South Sudanese than foreign nationals, and source some inputs locally, though they could become more important customers. NGOs employ one in five workers in businesses, and while UN and aid agency procurement is a minor source of demand in Juba, it is a major factor in smaller markets, for food and personal services. Business obstacles focus on insecurity, lack of demand (including due to inflation), no access to finance, and electricity. The study is one of a set of four reports assessing different aspects of jobs in urban South Sudan in order to formulate policy for recovery.